‘As if it Was Something Spoken by a Friend’: The Study of Digital Vote-Canvassing Networks on Facebook During the 2013 Bangkok Gubernatorial Election Campaign - Mukda Pratheepwatanawong (Center for Southeast Asian Social Studies (CESASS), 2018)
Adapting the idea of the traditional vote-canvassing network for the analysis of electoral politics in the digital arena and using the concept of ‘two-steps flow’, this paper explores the way in which Facebook was used to establish and develop ‘digital vote-canvassing networks’ during the 2013 Bangkok gubernatorial election campaign, which was the latest and a completed election in Thailand. This paper attempts to answer the question ‘How was the relationship among the individuals who were part of the candidates’ networks on social networking sites developed during the 2013 Bangkok gubernatorial election campaign?’ This research used multimodal analysis to determine the two main contenders’ strategy in expanding their Facebook network during the 2013 Bangkok gubernatorial election campaign. This research also conducted a total of 14 semi-structured interviews with Thai politicians, election candidates and their public relations personnel to examine the significant of relationship, interaction and spreadability of content on SNSs during the election campaign. This paper argues that the development of relationships among people connected to the digital vote-canvassing networks was integrated through the coordination and dissemination of campaign content on Facebook to enhance the electoral ties between candidates, their followers and followers’ friends, who might or might not be voters of the election. Vote-canvassing systems become ‘digital’ when a candidate’s public relations personnel acted as core vote-canvassers who manage and transmit campaign messages on the candidate’s Facebook page on behalf of the candidate, while the candidate’s followers interacted and spread the candidate’s campaign message to their own networks, enabling more Facebook users, who are connected to candidates’ Facebook page, in one way or another, to be exposed to the campaign content. However, there is no guarantee of votes in the digital vote-canvassing network.